Up Country - DeMille, Nelson (New York Warner Books, 2003)
One of the last things that Chief Warrant Officer Paul Brenner wanted to do was return to work for the Army's Criminal Investigation Division-an organization that thanked him for his many years of dedicated service by forcing him into early retirement. But when his former boss calls in a career's worth of favors, Paul finds himself having to do the last thing he ever wanted-return to Vietnam.
Keywords: Military offenses -- Murder--Investigation